MODERN MEANS OF STUDENTS’ FOREIGN LANGUAGE TRAINING OF TECHNICAL HIGHER EDUCATION INSTITUTIONS OF UKRAINE (Education in the 21st Century, 2023)
The article presents the interpretation of the concept «students’ foreign language training of technical institutions», which is considered as a complex process of forming by the means of a foreign language the ability of future specialists of technical industries to perform highly effective understanding and interaction with foreign interlocutors (in Ukraine and abroad) for personal and professional purposes, in written and oral forms, the ability to analyse and use various scientific and technical information presented in English-language sources of relevant fields for their usage in professional activity, the ability to use various dictionaries (printed and electronic) and more.It has been emphasized that the implementation of modern means of foreign language training for students of technical higher education institutions helps to build the educational process on such principles as: continuity of education; accessibility and individualization; consistency and systematicity; virtualization, etc.Various modern teaching means such as audio-visual and technical have been presented and analysed.Advantages of modern means implementation of students’ foreign language training of technical higher education institutions of Ukraine in the educational process have been characterized.